Application Of an Adaptive Auditory Model To Speech Recognition - Cohen, Jordan R. (Canadian Acoustics, 2022)
An adaptive model of the firing rates found in the auditory nervous system was configured as a signal processor for the IBM speech recognition system. The signal processor was tested on sentences drawn from office correspondence. Several experiments were done in low noise office environments using various microphones and different speakers. The system performance improved substantially compared to performance using a standard signal processor.